Figurative Language in the Broken Wings by Kahlil Gibran: An Analysis of Language Style as Stylistic Effect - Tira Nur Fitria (Universitas Ahmad Dahlan, 2022)
The objective of this research is to find out the figurative languages in the Broken Wings by Kahlil Gibran. This research is descriptive qualitative. The data was taken from Kahlil Gibran’s novel entitled “The Broken Wings”. The researcher analyzes the data based on Abrams’s theory (1999) about figurative language. The result analysis shows that Based on table 9 above, shows there are several types of figurative language in “The Broken Wings” by Kahlil Gibran. 292 data contains figurative language in 8 types of figurative language including simile, personification, metaphor, synecdoche, hyperbole, paradox, symbol, and proverb. In a simile, there are 128 data (43.8 %). In personification, there are 34 data (11.6 %). In metaphor, there are 33 data (11.3 %). In synecdoche, there are 30 data (10.3 %). In hyperbole, there are 25 data (8.6 %). In a paradox, there are 22 data (7.5 %). In symbol, there are 13 data (4.5 %). In the proverb, there are 7 data (2.4 %). It shows that the most dominant type of figurative language in “The Broken Wings” by Kahlil Gibran is simile as 128 data or 43.8 %. The novel Broken Wings by Kahlil Gibran is a romantic literary novel that tells the fate of Gibran's love story for a Lebanese girl named Selma Karamy. The writing of this novel is very light and easy to read and the way he writes it makes us immersed in the situation of the love story. The style of language used by the author in this novel is very distinctive. The author provides proof that his love story wrapped in romance is written in beautiful and interesting language to the readers.